Cumhuriyetten günümüze hükümet programlarında turizm - Esen, Şaban; Emir, Gökhan; Uyar Oğuz, Hande; Esen, Şaban; Oğuz, Hande Uyar; Emir, Gökhan (Detay Yayıncılık, 2012)
[Abstract Not Available]
Keywords: Turizm; Tourism